Ritual Pelian budaya masyarakat Iban di daerah Sebauh, Bintulu Sarawak - Tugau, Mangai; Magiman, Mohamad Maulana; Kundat, Franklin Ragai; Salleh, Norhuda (Association for Researcher of Skills and Vocational Training, 2021)
Pelian is a healing and spirit separation ritual between the dead and the living community among the Iban who are strongly upholding pengarap lamaor animism.The ritual Pelianhas a few objectives such as to insipid mimpi jaior nightmare, to heal patient, separation of spirit between the dead and the living community and the process of initation or ordination for a new Manangor shaman. The process of Pelian can only be performed by Manangorshaman with different objectives,customs and traditions according to the types of Pelianto be performed. The belief towards ritual Pelianstarted from the Iban believed that the world is divided into three parts namely this world, World of the Dead (Sebayan) and World in the sky. During the process of Pelian, the Manangor shaman is dealing with Raja Menjaya (King of Manang) to gain the healing power and the separation of spirit between the dead and the living community. There are fifty-six (56) types of Pelian. From those number of Pelian, the common Pelianperformed are Pelian Beserara Bungai(Separation of Spirit), Besudi(to ascertain the distress), Nimang Lupung Enggau Ubat(a blessing on Manang’smedical kits), Bebunuh(to kill buyuor incubus), Bebangun enggau Betimba(to initiate or to ordinant new shaman) and Mulai ke Semengat (to rescue the patient soul). The main focus of this article is to make a research on the ritual process of Pelianand to analyze the related symbols. Apart from that, it is to identify elements in Pelianwhich has become an identity to the Iban Community. This research was carried out by using qualitative method (ethnography) which includes Field Research / Field Work, Participant Observation, Interview and Library Research. The research area covers the whole of Sebauh District which includes area of Sebauh River, Pandan-Binyo River, Labang River and Tubau-Jelalong River. The data collected then being analyzed based on interpretive, descriptive, induction, Grounded Theory and also the believe and understanding of the community studied. Among the findings of this research are, Pelianis healing ritual to strengthen the ayuor ‘core being’ of a person and to separate the soul of the dead with the living community. Every Pelianis having its own functions and it differs from one another. The appointment or initation of Manangconsist of two ways namely appointment or initation made by Petaraor God through dream and inheritance from parents or other family members. The uniqueness of Manangor shaman in the process of Pelianis his ability to communicate with Petaraor God in Sebayan(World of Death) and in the sky. There are many types of symbols used in the process of Pelianlike piring(offering to God), pua kumbu’(woven blanket), knife, anak kebuk(small jar), manuk(chicken), kain sarung(strip of cloth worn round the body), pagar api (highly symbolic structure that forms the ritual centre). The uniqueness of its process and symbols used has made Pelianbecomes the identity of Iban Community.